2005
DOI: 10.1682/jrrd.2004.06.0071
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of quality of life in patients with localized prostate cancer undergoing radiotherapy

Abstract: This study prospectively evaluated quality of life (QOL) in localized prostate cancer patients undergoing radiotherapy, and it examined the relationships between QOL, depression, fatigue, and sleep disturbance. Instruments that were used are Functional Assessment of Cancer Therapy for Prostate (FACT-P), Beck Depression Inventory (BDI), Piper Fatigue Scale (PFS), and Epworth Sleepiness Scale (ESS). We evaluated patients at preradiotherapy (PRT), midway radiotherapy (MRT), completion of radiotherapy (CRT), follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 37 publications
8
35
0
5
Order By: Relevance
“…Such responses highlight the influence of these concerns in the low averages shown in the domains of emotional functioning (41.18) and role performance (51.40), corroborating other research that emphasized the importance of considering the domains of physical and psychological well-being, general well-being, and social and religious aspects when assessing the HRQoL of cancer patients (20) .…”
Section: Rev Esc Enfermsupporting
confidence: 83%
“…Such responses highlight the influence of these concerns in the low averages shown in the domains of emotional functioning (41.18) and role performance (51.40), corroborating other research that emphasized the importance of considering the domains of physical and psychological well-being, general well-being, and social and religious aspects when assessing the HRQoL of cancer patients (20) .…”
Section: Rev Esc Enfermsupporting
confidence: 83%
“…Younger age at diagnosis, high neuroticism, presence of pain, post-treatment co-morbidity and urinary and intestinal dysfunction were significantly associated with CF in the multivariate analysis, with the highest numerical point estimate for high neuroticism. Fatigue or loss of vitality, to a certain degree reflecting fatigue, has been reported in several surveys of prostate cancer survivors, [9][10][11][12][13] often assessed as a dimension of a generic QoL instrument such as the RAND 36-Item Health Survey (SF-36) or the EORTC QLQ C30. However, in most studies patients who never received ADT cannot be separated from those with previous or ongoing hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As ADT is highly associated with fatigue, 29,30 such separations are necessary when the role of local treatment is to be evaluated. Monga et al, 12 in a study meeting this requirement, found the rate of severe fatigue to be 40% among RAD patients with no initial ADT, at a mean time of 16.2 months after initiation of RAD, however, without identification of current hormone users. Our observations add to the results of these studies of fatigue in prostate cancer survivors, [9][10][11][12][13] showing that fatigue is a problem after local treatment even in patients without ADT.…”
Section: Discussionmentioning
confidence: 99%
“…The intensive, multi-modality treatments of chemotherapy drugs, radiation and surgery that have improved cancer survival often produce disruptive side effects that unexpectedly interfere with the patient's physical and mental functioning affecting their everyday QOL. [3][4][5] Often these disruptions may manifest themselves as perceived unmet needs that affect not only the individual's QOL but can also affect compliance to treatment regimens and thus impact individual long-term prognosis. As Puerto Ricans are one of the largest Hispanics groups in the US, [6,7] it is crucial that clinicians and researchers become skilled in assessing the prevalence of the perceived unmet needs of Puerto Rican cancer patients undergoing treatment to properly respond to their needs.…”
Section: Introductionmentioning
confidence: 99%